2022
DOI: 10.3390/socsci11100448
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Mechanisms Used to Improve Community Participation in the Integrated Development Planning Process in South Africa: An Empirical Review

Abstract: In 1996, the government of South Africa introduced the Integrated Development Plan (IDP) policy process to transform municipal administration, integrated planning and service delivery. One of the IDP policy’s key aspects is community participation in the planning process. South Africa is still struggling to achieve their duty of delivering basic services due to ineffective community participation. The article primarily appraises the mechanisms for improved community participation in the IDP process. It is unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…These results agree with those of Mamokhere and Meyer [50]'s study, which revealed that 48% of respondents in their sample in the Tzaneen local municipality in Mopani District were familiar with the IDP, one of the spatial planning tools. Mathebula, Nkuna and Sebola [51] associate this state of awareness to Mopani District's inability to include municipal residents in the participatory processes of management planning, formulation and implementation of the IDP, thereby impacting the awareness level of spatial planning tools for disaster risk reduction.…”
Section: Discussionsupporting
confidence: 90%
“…These results agree with those of Mamokhere and Meyer [50]'s study, which revealed that 48% of respondents in their sample in the Tzaneen local municipality in Mopani District were familiar with the IDP, one of the spatial planning tools. Mathebula, Nkuna and Sebola [51] associate this state of awareness to Mopani District's inability to include municipal residents in the participatory processes of management planning, formulation and implementation of the IDP, thereby impacting the awareness level of spatial planning tools for disaster risk reduction.…”
Section: Discussionsupporting
confidence: 90%
“…The South African government launched the Action Plan (NAP) in 2019 to facilitate the integration and embrace a humane and digni ed approach to managing migrants, refugees, and asylum seekers to ensure social cohesion and that foreigners receive the services they are entitled to. According to Mamokhere & Meyer (2022), the integration development planning must be based on the needs and priorities of the community, with opportunities for community involvement to identify the most pressing needs and allow all involved stakeholders to participate in the creation and execution of the plan.…”
Section: Involvement and Participation Of Foreign Migrants In The Idp...mentioning
confidence: 99%
“…The concept of IDP was identified as one of the perfect tools of planning to give effect to the shift from ad-hoc project-based approaches to a more strategic and integrated form, particularly in developing countries (Sibanda, 2018; Ramaano, 2022a; Mamokhere and Meyer, 2022a). IDP is a mechanism to drive a needs-based practice in which equity, institutional transformation and participatory management are stressed and has had a prolonged incubation involving the recycling and recombination of old and political contexts (Sibanda and Lues, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, it transformed the typical modernist planning system, which was rigid, into a more post-modern, democratic, strategic and developmental type of planning system (Biljohn and Lues, 2020; Ramaano, 2022c, d, e). On the other hand, it replaced the top-down segregation planning of the apartheid regime with bottom-up planning comprising the joint engagement of the public, private and voluntary sectors in local planning (RSA, 2000; Mamokhere, 2022; Mamokhere and Meyer, 2022c). To achieve this, municipalities were compelled, in terms of the Constitution of the Republic of South Africa (1996) and the Local Government: Municipal Systems Act (2000), to adopt IDPs to guide the planning and development across the entire municipal area (RSA, 1996, 2000).…”
Section: Introductionmentioning
confidence: 99%